Penerapan Model Discovery Learning Berbasis Assessment for Learning (AfL) dalam Pembelajaran Matematika Ditinjau dari Optimisme Siswa Kelas XI SMK Negeri 1 Banyudono - Oktora, Siwi Rimayani; , Dra. N Setyaningsih, M.Si; , M Noor Kholid, S.Pd., M.Pd (2015)
The aim of research to describe and analyze: (1) the effect of mathematics learning with Discovery Learning model and Discovery Learning model of Assessment for Learning (AfL) based to mathematics achievement, (2) the effect of student's optimism to mathematics achievement, (3) the interaction between learning model and student's optimism to mathematics achievement. The type of the research is experiment with quasi experimental design. The population of the research was all students of XI Grade of SMK Negeri 1 Banyudono of even semester of academic year 2014/2015. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use test, questionnaires and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect of Discovery Learning model and Discovery Learning model of Assessment for Learning (AfL) based to mathematics achievement, with , (2) there is effect of student's optimism for mathematics achievement, with , (3) there is no interaction between Discovery Learning model and Discovery Learning model of Assessment for Learning (AfL) based with student's optimism to mathematics achievement, with , 1.